Social Media Based Andragogical Learning in Islamic Religious Education: Inovasi Pembelajaran Pendidikan Agama Islam Berbasis Media Sosial Andragogi Digital - Aceng Aminullah; Elsa Selvia Febriani; Muhamad Zaenal Arifin; Yasmin Athira Hasania; Selamet Selamet (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: The rapid development of digital technology in the Industry 4.0 era has transformed educational practices, including Islamic Religious Education, which is increasingly required to adapt to technology-mediated learning environments. Specific Background: Social media platforms provide flexible and participatory learning spaces that are particularly suitable for adult learners when aligned with andragogical principles, although challenges remain in maintaining instructional quality and Islamic values. Knowledge Gap: Despite widespread use of social media in education, limited scholarly attention has been given to its integration with andragogy within Islamic Religious Education. Aims: This study aims to examine the integration of social media-based learning with an andragogical approach in Islamic Religious Education in the digital era. Results: The findings indicate that social media platforms such as Instagram, YouTube, and WhatsApp facilitate self-directed, experience-based, and problem-centered learning, while challenges include low digital literacy, misinformation, and the preservation of Islamic values. Novelty: This study presents a novel synthesis of andragogical theory and social media application specifically within Islamic Religious Education. Implications: The results provide practical guidance for educators to formulate clear social media usage guidelines, promote interactive learning environments, and strengthen digital literacy while adhering to Islamic teachings. Highlights • Social media supports self-directed and experience-based Islamic learning for adult learners• Andragogical principles align with interactive features of digital learning platforms• Digital literacy and value preservation remain central challenges in online Islamic education Keywords Islamic Religious Education; Social Media Learning; Andragogical Approach; Digital Era Education; Adult Learning